THE MERGER OF TOP UNIVERSITY- EXPLORING THE OPERATIONAL EFFICIENCY OF TAIWAN’S NYCU FROM A FINANCIAL PERSPECTIVE - Chiou Rung Chen, (PUPIL: International Journal of Teaching, Education and Learning, 2025)
This study utilized data envelopment analysis (DEA) to empirically evaluate the operational efficiency of Taiwan's top university NYCU from a self-financing perspective between 2012 and 2023. The results demonstrated that although the merged NYCU maintained increasing returns to scale (IRS) in research output, his teaching output transitioned to more severe decreasing returns to scale (DRS) beginning from the second year post-merger (2022). This shift, coupled with a simultaneous surge in four input factors—particularly administrative and general affairs expenses—drove NYCU's overall operations into increasingly severe scale inefficiency. The findings confirmed that the merger-induced diversity of fields, disciplines, and missions, along with the multi-campus structure, resulted in diseconomies of scale and scope. Additionally, the study identified NYCU's strong resilience against declining birthrate impacts, while noting that Taiwan's current public university tuition system undermined institutional financial stability and efficiency.